Orientasi Berbelanja Pakaian di Distro - Suliyanto, S; Wulandari, Siti Zulaikha (Jurnal Trikonomika, 2012)
The purpose of this study was to analyze the effect of shopping orientation towards the purchase of clothing in distro based on personality and gender. The samples were consumers who make purchases clothing in distro in Purwokerto. The sample size in this study was 100 respondents. Sampling is done by purposive sampling method. Analytical tool used are the path analysis and T- test independent samples. The results of this study were need for advice orientation, shopping for fun orientation has positive influence on shopping decisions on distro, while quick shopping orientation has not positive influence both in extrovert and introvert personality, both in male and female respondents. There were no differences, need for advice orientation, quick shopping orientation and shopping for fun orientation between extrovert and introvert personality. Need for advice orientation dan quick shopping orientation maleâs were higher than its female but shopping for fun orientation femaleâs was higher that its male.